A preschool program for safety and injury prevention delivered by home visitors. Issue 4 (1st December 2000) - Johnston, B D; Britt, J; D'Ambrosio, L; Mueller, B A; Rivara, F P
Abstract : Objective —To evaluate the feasibility, acceptability, and effectiveness of an injury prevention program delivered by school based home visitors to the families of low income children attending preschool enrichment programs in Washington State. Study sample —The families of children attending preschool Head Start programs in two regions were eligible. A total of 213 families (77.8% of those eligible) from intervention sites, and 149 families (71.9% of those eligible) from concurrent comparison sites, agreed to participate and completed the trial. Intervention —Trained school personnel conducted home safety inspections as part of a planned home visit. Intervention families were offered educational materials as well as smoke detectors, batteries, ipecac, and age appropriate car safety restraints based on results of the home inspection. Evaluation methods —At a repeat home visit three months later, the proportion of families with a positive change in injury prevention knowledge or behavior among those in the intervention group was compared with the proportion in the comparison group. Smoke detector presence and function were observed. Results —Among families without a working smoke detector at baseline, the intervention was associated with an increased probability of having a working detector at follow up (relative risk (RR) 3.3, 95% confidence interval (CI) 1.3 to 8.6). Intervention families were also more likely to report the presence of ipecac in the home (RR 4.7, 95% CI 3.0 to 7.3) at follow up and to have obtained an age appropriate booster seat (RR 4.1, 95% CI 1.9 to 8.8). The program was acceptable to client families and to the home visitors who conducted the intervention. Conclusions —Among the families of low income children enrolled in preschool enrichment programs, home safety inspections and the distribution of safety supplies by school based home visitors appears to improve knowledge and behavior related to poisoning, smoke detector installation, and car safety seat use over three months of follow up.